Onboarding handbook: An indispensable tool for onboarding processes - Teresa Godinho; Isabel Pinto Reis; Rui Carvalho; Filipa Martinho (Administrative Sciences, 2023)
Onboarding handbooks constitute a very important and powerful tool in the socialization and integration processes of recruits implemented by Human Resources. As companies compete to thrive in global markets, the attraction and retention of employees have been given much attention in recent years. One of the strategies developed by companies to achieve this goal are the so-called Onboarding Handbooks given to newcomers, serving as a means of facilitating workers' integration into the everyday processes of the company. As a consolidated research area, many HR studies have been developed around these subjects, as these manuals have been proven to be important tools in the socialization process of the former candidate, now entering the organisational culture of a given enterprise. A literature review was developed according to the main variables of the study of Organisational Socialization processes, strategies, and methods, with special emphasis on the onboarding book. To find out if these manuals correspond to the relevant literature of HR, eight of the onboarding handbooks from several public and private organizations have been analysed following the proposed structure of onboarding handbooks presented in the literature review. In addition, purposeful sampling was followed and content analysis on the handbooks was developed. The paper's contributions are twofold: (a) the authors suggest a complete and up-to-date structure for the contents of onboarding books to be applied by HR managers and (b) compare its structure to several manuals of different enterprises from various sectors of the Portuguese economy. Findings show that the onboarding book remains an important tool and facilitator of organisational integration. Although, the onboarding processes are changing, and even the format of the onboarding books can become different (digital or not), their contents are essential for the socialization of newcomers and a means to organisational culture dissemination as well as containing functional contents such as internal norms and regulations.
Keywords: 350; employee integration; human resources; onboarding handbook; organisational culture; organisational socialization